Computational exploration, Hirshfeld Surface Analysis, Molecular Dynamics Simulation, ADMET Profiles, and Molecular Docking of 3a,8a-Dihydroxy-1-phenyl-1,3, 3a,8a-tetrahydro-indeno[1,2-d] imidazole-2,8-dione - Tanveer Hasan; Raza Murad Ghalib; Sayed Hasan Mehdi; Pramod Kumar Singh; Syed Asad Ali; Arman Taqvi; Nazia Kazmi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this work, a detailed study of 3a,8a-tetrahydro-indeno[1,2-d] 3a, 8a-Dihydroxy-1-phenyl-1,3-imidazole-2,8-dione [C16H12N2O4] [NPU] bearing anticarcinogenic effect was examined using quantum computational method. The compound's equilibrium geometry has been derived and examined using the DFT-B3LYP/LANL2DZ approach. FT-IR analysis was employed to recognize the different functional groups, and the outcomes are contrasted with the simulated spectra. Theoretical examination was conducted on the oscillation modes. The electronic characteristics, including HOMO and LUMO energies and the corresponding frontier energy band gap, were determined. Predictions of molecular electrostatic potential surface was carried out to examine the electrophilic and nucleophilic sites. Electrical properties viz. dipole moment, molecular polarizability, and first static hyperpolarizability have been employed to forecast the biological characteristics of the molecule. The analysis of the Hirshfeld surface has been conducted to examine the weak interactions present in the molecule. A molecular dynamics simulation of 100 ns was performed, assessing models through RMSD, RMSF, Rg, PC1-PC2-plot metrics, and the MMPBSA/MMGBSA tool was employed for calculating free energy. The proteins 4WNT and 4XRZ have undergone molecular docking analysis with the tile ligand molecule. The drug-likeness and ADMET factors were calculated to examine their medicinal properties.
Keywords: Molecular Dynamics Simulations; ADMET; DFT; Hirshfeld Surface; Molecular Docking